Islam and democracy : what is the real question? - Bayat, Asef (ISIM papers, 2007)
Is Islam compatible with democracy? The text examines one of the most frequently-asked and yet misguided questions. Democratic ethos should not and cannot be deduced from some essence of religions supposedly inscribed in the scriptures. Rather, they are the outcome of political struggles that push Islam toward democratic or authoritarian directions. Asef Bayat offers a new approach to examine Islam and democracy arguing how the social struggles of diverse Muslim populations, those with different interests and orientation, render Islam to embrace democratic ideas or authoritarian disposition. "Islamism" and "post-Islamism" are discussed as representing two contrasting movements which have taken Islam into different, authoritarian and inclusive, political directions. This title can be previewed in Google Books - http://books.google.com/books?vid=ISBN9789053569832